2018
DOI: 10.1371/journal.pone.0195902
|View full text |Cite
|
Sign up to set email alerts
|

The effects of unexpected mechanical perturbations during treadmill walking on spatiotemporal gait parameters, and the dynamic stability measures by which to quantify postural response

Abstract: Most falls occur after a loss of balance following an unexpected perturbation such as a slip or a trip. Greater understanding of how humans control and maintain stability during perturbed walking may help to develop appropriate fall prevention programs. The aim of this study was to examine changes in spatiotemporal gait and stability parameters in response to sudden mechanical perturbations in medio-lateral (ML) and anterior-posterior (AP) direction during treadmill walking. Moreover, we aimed to evaluate whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
74
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 39 publications
12
74
3
Order By: Relevance
“…Since the CoM velocity is closely related to the perturbation magnitudes, this suggests that, in regard to step length, our participants demonstrated more flexible behavior. In their review, Brujin and van Dieën [39] showed a large body of evidence suggesting that lateral recovery stepping is regulated based on the CoM state in the preceding swing phase, i.e., foot placement adjustments post perturbation were correlated with CoM velocity [29,38,52,53], and that compensatory step adjustments were actively generated [20]. For example, it was found that in mechanical perturbations in the mediolateral direction during walking, a larger lateral foot placement was associated with gluteus medius activity during the swing phase and the mediolateral movement of the CoM [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the CoM velocity is closely related to the perturbation magnitudes, this suggests that, in regard to step length, our participants demonstrated more flexible behavior. In their review, Brujin and van Dieën [39] showed a large body of evidence suggesting that lateral recovery stepping is regulated based on the CoM state in the preceding swing phase, i.e., foot placement adjustments post perturbation were correlated with CoM velocity [29,38,52,53], and that compensatory step adjustments were actively generated [20]. For example, it was found that in mechanical perturbations in the mediolateral direction during walking, a larger lateral foot placement was associated with gluteus medius activity during the swing phase and the mediolateral movement of the CoM [38].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that commonly occurring, clinically important falls Gerontology 2020;66:362-370 DOI: 10.1159/000505649 related to walking are unexpected, and may have greater injury potential in a lateral direction. While most research on balance reactive control has focused on perturbations during standing [7,9,10], there is now a large body of literature on reactive balance to perturbations during walking specifically in response to anterior-posterior perturbations [11][12][13][14][15][16][17][18][19][20][21][22]. Less data exist evaluating responses to lateral loss of balance while walking.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless among healthy adults, both high-and low-variability can be associated with gait stability indicating that other factors may also be at play in producing instable gait (Beauchet et al, 2009). Variability and changes in variability may also reflect the adaptability of gait and its adaptions to environmental demands (Madehkhaksar et al, 2018). Therefore, the context and subject in question must be considered when assessing movement from this perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Of several previous studies examining the kinematic properties of balance recovery [8][9][10], some have demonstrated that the stabilization of walking speed and stepping frequency following perturbation is a two-stage process [[11] [12]. The first stage (initial response) is aimed at reducing the perturbation effect to minimum, the second stage is a gradual return to steady state.…”
Section: Introductionmentioning
confidence: 99%
“…Hof and colleagues have proposed that accurate generation of step length and step width will optimize the required timing and placement of the extrapolated center of mass within the base of support [8,9]. Recently, Madehkhaksar et al [10] found that in order to increase dynamic stability immediately after perturbation, young adults walk with shorter, wider strides and a higher cadence, with a stronger response to medio-lateral than to anterior-posterior perturbations. Vlutters et al [14] found similar results when applying perturbations to the hip during walking stating that "at heel strike after the perturbation, recovery from medio-lateral perturbations involved medio-lateral foot placement adjustments proportional to the medio-lateral center of mass velocity.…”
Section: Introductionmentioning
confidence: 99%